Propofol Sedation by Pediatric Gastroenterologists for Endoscopic Procedures: A Retrospective Analysis - Khalila, Aya; Shavit, Itai; Shaoul, Ron (Frontiers in Pediatrics, 2019)
Background: There is a substantial literature on the favorable outcome of propofol administration by non-anesthesiologists for endoscopy in adults; however, very few data are currently available on propofol sedation by pediatric gastroenterologists. Aims: to evaluate the safety of propofol sedation by pediatric gastroenterologists. Methods: A retrospective chart review of all children who were sedated by pediatric gastroenterologists in three Northern Israeli hospitals over a four year period Demographic and medical characteristics and any data regarding the procedure were extracted from patient's records. The main outcome measurements were procedure completion and reported adverse events. Results: Overall, 1214 endoscopic procedures for were performed during this period. Complete data was available for 1190 procedures. All children sedated by pediatric gastroenterologists were classified as ASA I or II. Propofol dosage (in mg/kg) inversely correlated with patient age. The younger the child the higher the dose needed to reach a satisfactory level of sedation (r=-0.397,p<0.001). The addition of fentanyl significantly decreased propofol dosage needed to provide optimal sedation, p <0.001. Nine (0.7%) reversible adverse events were reported. All the procedures were successfully completed and all patients were discharged home. Conclusions: We conclude that our approach is safe in children as it is in adults and can be implemented for children with ASA I, II.